Penerapan Total Quality Management (TQM) dalam Meningkatkan Kualitas Pelayanan Rumah Sakit - Farah Chalida Hanoum; Fajar Gumilang Kosasih; Ratna Tri Hari Safariningsih (LPPM Institut Nasional Laa Roiba Bogor, 2022)
TQM is one of the modern management concepts that strives to respond appropriately to any changes. TQM method is a method that is carried out in an effort to improve the quality, one of which is in the performance of hospitals in improving the quality of services in order to improve the quality of public hospital services, the management should try to carry out and synergize the hospital's integrated quality management based on the availability of facilities and services medical equipment supported by medical personnel who are quite reliable in their fields. Steps taken by the hospitali, among others, working with the government, opening up opportunities for relationships partnership for foreign investors to develop this hospital to be better in the future. Keywords: TQM, Service Quality.